2018
DOI: 10.3892/or.2018.6759
|View full text |Cite
|
Sign up to set email alerts
|

Pectolinarigenin inhibits non‑small cell lung cancer progression by regulating the PTEN/PI3K/AKT signaling pathway

Abstract: Lung cancer is the principal cause of cancer-associated mortality. Pectolinarigenin (Pec) reportedly has effective antitumor activity against certain cancer types. Phosphatase and tensin homolog (PTEN) is a well-known tumor suppressor and serves a vital role in cancer progression. However, the effect of Pec on non-small cell lung cancer (NSCLC) cell proliferation and metastasis, and the underlying mechanism, has not yet been elucidated. In the present study, it was demonstrated that Pec inhibited the prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Pectolinarigenin was shown to be active against different cancer cell lines [37][38][39][40][41]. To date and to our knowledge, only one study described its anticancer potential on RCC cells (ACHN) with an IC 50 value of 15.2 µM [42].…”
Section: Subfractions Compound Code T R (Min) λMax (Nm) [M-h]mentioning
confidence: 99%
See 1 more Smart Citation
“…Pectolinarigenin was shown to be active against different cancer cell lines [37][38][39][40][41]. To date and to our knowledge, only one study described its anticancer potential on RCC cells (ACHN) with an IC 50 value of 15.2 µM [42].…”
Section: Subfractions Compound Code T R (Min) λMax (Nm) [M-h]mentioning
confidence: 99%
“…To date and to our knowledge, only one study described its anticancer potential on RCC cells (ACHN) with an IC 50 value of 15.2 µM [42]. The effects of pectolinarigenin on the viability of SK-HEP-1, SMMC-7721 and PLC5 liver cancer cells were also reported (IC 50 values of 10, 11.59 and 11.97 µM, respectively) [39][40][41] as well as on A549 and Calu-3 lung cancer cells (IC 50 values of 21.49 and 22.63 µM, respectively) [40], SW620 colon cancer cells (IC 50 = 13.05 µM) and KATO-III, AGS and MKN28 gastric cancer cells (IC 50 of 24.31, 124.79 and 96.88 µM, respectively) [37,38].…”
Section: Subfractions Compound Code T R (Min) λMax (Nm) [M-h]mentioning
confidence: 99%
“…Phosphatase and tensin homolog (PTEN) has been appreciated as an important tumor suppressor and to oppose phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) pathway in human cancers [12]. Accruing works have revealed that PTEN is involved in progression of cancers and negatively correlated with AKT signaling in hypopharyngeal carcinoma, non-small cell lung cancer and esophageal squamous cell carcinoma [13][14][15]. Previous study suggested that loss of PTEN is associated with progression of papillary thyroid cancer [16].…”
mentioning
confidence: 99%
“…As a typical candidate, flavonoids have exhibited potential for cancer suppression through apoptosis induction and other different mechanisms, such as autophagy induction ( 20 , 21 ). Pectolinarigenin is a natural extract from multiple herbal medicinal plants, including Cirsium japonicum, Eupatorium odoratum and Trollius chinensis ( 22 ). Previous studies have reported that pectolinarigenin demonstrates potent inhibitory activity on melanogenesis and effective antitumor activity in vivo and in vitro ( 10 , 15 ).…”
Section: Discussionmentioning
confidence: 99%